2007
DOI: 10.1016/j.clae.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study: Methods and findings to date

Abstract: Purpose-To describe baseline and longitudinal findings of the Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study.Methods-The CLEK Study is an eight-year, multi-center, natural history study of 1,209 patients with keratoconus who were examined annually for eight years. Its goals are to prospectively characterize changes in vision, corneal curvature, corneal status, and vision-specific quality of life.Results-CLEK Study subjects had a mean age at baseline of 39.3 +/− 10.9 years. At study entry, 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
213
3
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(246 citation statements)
references
References 25 publications
13
213
3
17
Order By: Relevance
“…However, de Lavalette et al (17) reported a female predominance of 65% in their study. Various studies have reported that keratoconus has an equal prevalence in both genders, (1,18) a greater prevalence in males, (14)(15)(16)19) and a greater prevalence in females. (20) One possible reason for the increased relative frequency of male subjects undergoing transplantation compared with female subjects is an increased tendency for males to receive surgical treatment so as to improve occupational performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, de Lavalette et al (17) reported a female predominance of 65% in their study. Various studies have reported that keratoconus has an equal prevalence in both genders, (1,18) a greater prevalence in males, (14)(15)(16)19) and a greater prevalence in females. (20) One possible reason for the increased relative frequency of male subjects undergoing transplantation compared with female subjects is an increased tendency for males to receive surgical treatment so as to improve occupational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduced rate of progression of KC with increasing age, KC can progress in older patients, resulting in reduced visual acuity and quality of life. 1,[6][7][8] Whether iatrogenic CXL in older adults with naturally cross-linked corneas has the same positive effect as in younger adults is unknown. A recent study on the safety of CXL found that age Z35 years was a major risk factor for adverse events after CXL.…”
Section: Introductionmentioning
confidence: 99%
“…1 Corneal cross-linking (CXL) using riboflavin and ultraviolet-A light has been shown to effectively increase corneal stiffness and even to reduce ectasia. [2][3][4] These findings originate from studies done mainly in young adults and led to the widespread use of CXL to stabilize KC in this group of patients, who have a 20% risk of progressing to a stage that requires therapeutic keratoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Bei unilateralem KC kann sich auch am sog. guten Auge (Auge mit forme fruste KC) in einem Teil der Fälle ein progredienter KC entwickeln [9], es kann jedoch auch stabil bleiben [10]. [19] in Verbindung mit der Spaltlampe eine Hornhauttopographie und Ultraschallpachymetrie an.…”
Section: Definitionunclassified